Imaging based risk factors for heart failure death in childhood dilated cardiomyopathy: a systematic review and meta-analysis - Street-de Palma, Christina; Lim, Zhia; Field, Ella; Kaski, Juan Pablo; Norrish, Gabrielle (Frontiers in Cardiovascular Medicine, 2025)
Background and aimDilated cardiomyopathy (DCM) is the most common heart muscle disease presenting in childhood and is associated with an increased risk of heart failure related death. In adult cohorts, imaging characteristics such as increased left ventricular dimensions or the presence of fibrosis on cardiac magnetic resonance imaging (MRI) have been shown to be associated with adverse outcomes. In contrast, the prognostic relevance of imaging characteristics in childhood cohorts remains unclear and predicting disease progression is challenging. The aim of this study was to perform a systematic literature review and meta-analysis of imaging characteristics associated with adverse outcomes in childhood DCM.MethodsPubMed, Embase, and Scopus databases were searched for original articles published in English from 1946 to July 2024 that included patients under 21 years with a confirmed diagnosis of DCM and primary or secondary end-points of heart failure death or equivalent event (heart transplantation or ventricular assist device implantation). Studies were excluded if imaging characteristics were not described.ResultsThirteen studies (1,348 patients) met the inclusion criteria. All but one study was retrospective and only one had a patient cohort of more than 100 patients. We identified four imaging risk factors that were evaluated in at least four studies and significantly associated with a heart failure end point in at least two; left ventricular end-diastolic diameter Z score (LVEDD) [pooled hazard ratio [HR] 1.43, 95% confidence interval [CI] 1.13–1.81, p = 0.003], left ventricular ejection fraction (LVEF) (pooled HR 0.8, 95% CI: 0.65–0.99, p = 0.04), LV fractional shortening (LVFS) and severe mitral regurgitation (MR) [pooled odds ratio (OR) 5.12, 95% CI: 1.18–22.19, p = 0.004]. Two small studies investigated the role of fibrosis on CMRI and did not report an association with adverse outcomes.ConclusionsA systematic review and meta-analysis of imaging risk factors predicting heart failure adverse events in childhood DCM was performed identifying three “major” risk factors; higher LVEDD, lower LVEF or LVFS and severe MR. The findings highlight a significant need for well-designed multicentre studies to investigate the role of imaging characteristics in predicting outcome in the paediatric population.